Direct relationship of local C-reactive protein production and lipid pool characterized by integrated backscatter intravascular ultrasound: a preliminary observation. Issue 5 (August 2015) - Kobayashi, Yuhei; Okura, Hiroyuki; Kume, Teruyoshi; Miyamoto, Yoshinori; Yamada, Ryotaro; Kobayashi, Yukari; Fukuhara, Kenzo; Koyama, Terumasa; Neishi, Yoji; Yoshida, Kiyoshi
Abstract : Background: Local production of C-reactive protein (CRP) in human coronary arterial plaque was reported as a possible marker for local inflammation and vulnerable plaque. Integrated backscatter intravascular ultrasound (IB-IVUS) plaque tissue characterization may detect vulnerable plaque with high local plaque inflammation. Thus, the aim of this study was to clarify the relationship between IB-IVUS-based plaque characteristics and local high-sensitivity C-reactive protein (hs-CRP) production in stable and unstable plaque. Methods and results: Eighteen patients (nine unstable angina/non-ST-segment elevation myocardial infarction and nine stable angina) were prospectively enrolled. Using the microcatheter, blood samples from the proximal and distal sites of the culprit lesion were obtained to measure local CRP production. Translesional hs-CRP was defined as distal hs-CRP minus proximal hs-CRP of the culprit lesion. Gray-scale and IB-IVUS analyses were carried out at the target lesion. The translesional hs-CRP level tended to be higher in the unstable angina group than in the stable angina group (0.026±0.033 vs. 0.003±0.007 mg/dl, P =0.050). Gray-scale IVUS-derived indices did not correlate with translesional hs-CRP. However, % lipid pool area by IB-IVUS correlated positively ( r =0.54, P =0.02) and % fibrosis area correlated negatively with the translesional hs-CRP level ( r =−0.52, P =0.03). Conclusion: Lipid pool area detected by IB-IVUS is correlated positively with the translesional hs-CRP level. Abstract : Supplemental Digital Content is available in the text.